Why pay more? Corporate Tax Avoidance through Transfer Pricing in OECD Countries - Eric J. Bartelsman; Roel Beetsma (Tinbergen Institute, 2000)
This paper presents suggestive evidence of income shifting in response to differences in corporate tax rates for a large selection of OECD countries. We use a new method to disentangle the income shifting effects from the effects of tax rates on real activity. Our baseline estimates suggest that a substantial share of the revenues from a unilateral increase in the corporate tax rate is lost because of a decline in reported income.
Keywords: F2; H2; 330; Profit shifting; Transfer pricing; Corporate tax rates; STAN database; Verrechnungspreis; Unternehmensbesteuerung; Steuervermeidung; Steuereinnahmen; OECD-Staaten